Pengaruh Rasio Profitabilitas Dan Rasio Aktivitas Terhadap Nilai Perusahaan Pada Perusahaan Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2022 - Nur Rahmawati, Desy; Erica, Denny; Rachmah , Siti Mabrur (Program Studi Sistem Informasi Akuntansi Kampus Kota Sukabumi, 2023)
The presence of telecommunications services is needed in the digitalization era to activate increasingly sophisticated telecommunications equipment. The development of the telecommunications sub-sector can already be seen from the large number of people using telecommunications equipment. Several telecommunications companies operating in Indonesia are listed as issuers on the Indonesia Stock Exchange. Telecommunications companies must be able to compete and improve their performance in order to maintain high corporate value in the eyes of investors. The purposes of this study are: 1. To test how the influence of the profitability ratio on firm value in telecommunications companies listed on the Indonesia Stock Exchange (IDX) for the 2022 period 2. To test how the effect of the activity ratio on firm value in telecommunications companies listed on the Stock Exchange Indonesia (IDX) for the 2022 period. The data collection technique in this study used secondary data. This study obtains data through storage, where a collection of information is obtained from documents such as records, financial reports, and others. The data used is obtained from the official website of the Indonesia Stock Exchange (IDX). This shows that the return on equity has a significant effect on the price to book value. The coefficient value (Sig2) on the variable X2 is 0.398. This shows that in the case of total assets turnover (X2) it has a significant effect on price to book value (Y).